Dean Mosman letter to Nicholas S. Halmi regarding bird sightings, Febuary 11, 1978 - Mosman, Deanet al (1978)
Letter from Dean Mosman to Nicholas S. Halmi regarding bird sightings, February 11, 1978. The following sightings are noted: a Red-Shouldered Hawk, Loggerhead Shrikes, Northern Shrikes, Common Redpolls, and Snow Buntings. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed